Liver Transplantation for Cirrhosis in Cystic Fibrosis - T Lamireau; S Martin; M Lallier; JE Marcotte; F Alvarez (Canadian Journal of Gastroenterology)
BACKGROUND: Liver disease is the third most common cause of death in children with cystic fibrosis (CF). Liver transplantation is an effective treatment in children with hepatic failure.